Proliferaciones de Pseudo-nitzschia spp. (Bacillariophyceae) y otras especies del microplancton en la Bahía de Mazatlán, México - Gómez-Aguirre, Samuel (2004)
Observations on microplankton in the autumn of 1996 revealed the existence of high densities of Pseudo-nitzschia spp. A similar phenomenon was found in November 1998 and November 1999 and a month later it shifted to the southern Mazatlán Bay while in California, USA, incidents of the poisoning of sea mammals were being recorded; this also happened on the Mexican Pacific coasts from January to March. Water samples collected at surface (<0.5 m deep) and subsurface (10 m deep) monthly, from November 1998 to January 1999 and every week from February 1999 to May 2000, were analyzed by the Utermöhl technique at 400 enlargements. Phytoplankton quantification showed winter and summer pulses; the 1998-1999 period was higher than the 1999-2000 period. Five species of Pseudo-nitzschia were identified by electron microscopy (TEM and SEM); a new study has revealed other species. High values of Pseudo-nitzschia were observed: 730 P-n/ml (Dec. 1999), 610 P-n/ml (Dec. 1998), 335 P-n/ml (Jul. 1999), 198 P-n/ml (Feb. 1999), 170 P-n/ml (Nov. 1998), 123 P-n/ml (Mar. 1999), 108 P-n/ml (Aug. 1999). The blooms of other species of diatoms (Thalassiosira spp., Asterionellopsis glacialis, Chaetoceros spp., Skeletonema costatum), dinoflagellates (Prorocentrum spp., Scripsiella trochoidea) and ciliates (Myrionecta rubra) were also observed.